2012
DOI: 10.1111/j.1571-9979.2012.00350.x
|View full text |Cite
|
Sign up to set email alerts
|

East Asians’ Social Heterogeneity: Differences in Norms among Chinese, Japanese, and Korean Negotiators

Abstract: East Asian cultures are widely held to be fairly homogeneous in that they highly value harmonious social relationships. We propose, however, that the focus (dyadic versus group) and the nature (emotional versus instrumental) of social relations vary among the Chinese, Japanese, and Korean cultures in ways that have important implications for the negotiation tactics typically employed by managers from these three cultures. Our data are from a web survey administered to three hundred eighty‐eight managers from C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…The process of building interpersonal relations varies across cultural settings, for example, guanxi in China, blat in Russia (Panina & Bierman, 2013), wasta in the Arab world (Khakhar & Rammal, 2013), wa in Japan, and inhwa in Korea (Lee, Brett, & Park, 2012).…”
Section: Expatriate Relational Abilitymentioning
confidence: 99%
“…The process of building interpersonal relations varies across cultural settings, for example, guanxi in China, blat in Russia (Panina & Bierman, 2013), wasta in the Arab world (Khakhar & Rammal, 2013), wa in Japan, and inhwa in Korea (Lee, Brett, & Park, 2012).…”
Section: Expatriate Relational Abilitymentioning
confidence: 99%
“…Some scholars have observed that attitudes regarding various negotiation tactics will be nuanced and diverse even within high-context cultures (Lee, Brett, & Park, 2012). For example, Chinese negotiators tend to employ emotional-appeal distributive tactics, while their Japanese counterparts tend to approve the use of integrative and distributive tactics (Lee et al, 2012). Other scholars noted that there are few empirical researches regarding the negotiation values of the Chinese (Sardy, Munoz, Sun, & Alon, 2010), hence making it challenging to understand how the Chinese perceive ethical negotiation concerns.…”
Section: Introductionmentioning
confidence: 97%
“…Some scholars have observed that attitudes regarding various negotiation tactics will be nuanced and diverse even within high-context cultures (Lee, Brett, & Park, 2012). For example, Chinese negotiators tend to employ emotional-appeal distributive tactics, while their Japanese counterparts tend to approve the use of integrative and distributive tactics (Lee et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Deletion of all items of the Equity construct can be explained by cultural differences between Korea and Japan. According to recent previous studies (e.g., Lee, Brett, & Park, 2012), Koreans tend to be more and more individualistic toward organizations, whereas the Japanese still tend to be collectivistic toward organizations. Because groups with underlying individualistic values tend to appreciate harmony and equity less than collectivistic groups (Hofstede, 1980;Kim, Park, & Suzuki, 1990), it seemed that the Equity construct in the Korean sample was not detected as a salient factor as in the Japanese one.…”
Section: Discussionmentioning
confidence: 87%